Jornalismo e redes sociais digitais: o Facebook na produção jornalística do site Repórter Parintins - Silva Júnior, Jonathas Muniz da (Brasil, 2022)
This work presents an overview of the use of digital social networks in journalistic production, seeking to relate the use of the internet through Facebook to the effects caused in a connected society, since such networks have attracted an increasingly considerable percentage of users. The study aims to analyze how digital social networks influence the production and dissemination of information in the city of Parintins/AM, through an analysis of the Repórter Parintins website. To this end, the monographic research starts from a literature review, which seeks to elaborate an overview of the evolution of the media, passing through print media, radio and television, until the arrival of the internet, exposing the phases, characteristics of digital journalism, the relationship between journalism and interaction with digital social networks. In this way, it places emphasis on understanding how the interaction with the public on the internet works, ending with the relationship between journalism and Facebook. To understand how this digital social network can assist in journalistic production in the context studied, in the city of Parintins, in Baixo Amazonas, the methodology also involves a case study about the Repórter Parintins website, developed from April 01 to 07, 2022 The study reveals that, nowadays, digital social networks are of great importance for journalistic newsrooms, especially regarding their potential for disseminating information. The research also shows that, despite all the potential offered in the digital environment, the Repórter Parintins website does not explore them so vehemently, leaving the Facebook page to become a mere transposition of the website, exploring in a basic way interactivity, customization or personalization, hypertextuality, multimediality, memory, instantaneity and ubiquity made possible in this network.